2003
DOI: 10.1080/00050060310001707167
|View full text |Cite
|
Sign up to set email alerts
|

The UK perspective: a review of research on organisational stress management interventions

Abstract: There are an increasing number of studies that have monitored the impact of Stress Management Interventions (SMls) and the results of these studies can play a vital role in informing the development of more effective, evidenced‐based SMIs. In this paper, the authors have undertaken a review of United Kingdom (UK)‐based research that has tested the impact of SMIs. Sixteen studies were examined and the results revealed that the vast majority of interventions were targeted at the individual employee, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 28 publications
3
108
0
2
Order By: Relevance
“…This is similar to results of other reviews, such as the one conducted by Van der Klink, Blonk, Schene, and van Dijk (2001), who found that organizationally focused interventions were implemented in only 5 out of 48 studies. The United Kingdom review study conducted by Giga et al (2003), who used search parameters similar to those used in this study, found that, of all post-1990 studies reviewed that received a three-star rating or higher, only 19% were organization-level interventions. Such results are consistent with Kompier, Cooper, and Geurts's (2000) suggestion that work stress programs are predominantly reactive (i.e., secondary or tertiary approaches) and tailored to the individual.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to results of other reviews, such as the one conducted by Van der Klink, Blonk, Schene, and van Dijk (2001), who found that organizationally focused interventions were implemented in only 5 out of 48 studies. The United Kingdom review study conducted by Giga et al (2003), who used search parameters similar to those used in this study, found that, of all post-1990 studies reviewed that received a three-star rating or higher, only 19% were organization-level interventions. Such results are consistent with Kompier, Cooper, and Geurts's (2000) suggestion that work stress programs are predominantly reactive (i.e., secondary or tertiary approaches) and tailored to the individual.…”
Section: Resultsmentioning
confidence: 99%
“…Kompier and Cooper (1999) systematically evaluated 11 organizational case studies from 11 different European countries. A more recent review of United Kingdom-based stress management interventions evaluated studies published in the academic literature over the past 10 years (Giga, Noblet, Faragher, & Cooper, 2003) and identified 16 studies.…”
mentioning
confidence: 99%
“…For those on sick leave at the time of inclusion, the intervention group has a median registration of 14.5 weeks (range [10][11][12][13][14][15][16] in DREAM, compared to a median of 16 weeks (range 12-16) for the WLC group (P=0.27). Changes in the rate of lasting return to work (or equivalent) are presented in figure 2 for the 60 participants who were on sick leave at randomization.…”
Section: Supplementary Analysismentioning
confidence: 99%
“…Cognitive behavioral stress management interventions often use only psychological outcomes (8)(9)(10). In a recent review, 4 out of 36 studies used absenteeism as an endpoint; none of these used a cognitive behavioral approach (8).…”
mentioning
confidence: 99%
“…Research by Giga et al (2003b) found that in only three out of sixteen research studies on organisational stress did management interventions focus on primary stress intervention. It is clear that empowering the individual worker to handle stressful work situations (second and third levels of intervention) does not succeed in promoting workers' health and wellbeing without having strategies in place which address organisational stressors (Cooper & Cartwright, 1997, as cited by Giga, Cooper & Faragher, 2003a).…”
Section: Stress Stressors and Intervention Strategiesmentioning
confidence: 99%